Pengembangan suplemen bahan ajar akhlak terhadap diri dan sesama manusia untuk Sekolah Dasar - Ubaidah; Andriana, Nesia; Widyasari (Tawazun: Jurnal Pendidikan Islam, 2024)
Education is a conscious and planned effort to create a learning atmosphere that supports the development of students’ potential, including noble morals. Morals are the main indicator in assessing the quality of a person, where morals in accordance with Islamic guidance reflect a commendable personality. This study aims to develop morals teaching material supplements for elementary school students that focus on the formation of morals towards themselves and fellow humans. The research uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: needs analysis, initial design, development through expert validation, implementation with practitioner suggestions, and final evaluation. The results showed that the developed teaching material supplement obtained feasibility scores from linguists (87%), material experts (91%), design experts (95%), and teachers (84%), with an overall average of 89%. The conclusion of this study is that the morals teaching material supplement developed is feasible to use to improve students’ understanding of morals learning in elementary schools. Keywords: Moral Education; Teaching Material Development; Elementary School Abstrak Pendidikan merupakan usaha sadar dan terencana untuk mewujudkan suasana belajar yang mendukung pengembangan potensi peserta didik, termasuk akhlak mulia. Akhlak menjadi indikator utama dalam penilaian kualitas seseorang, di mana akhlak yang sesuai tuntunan Islam mencerminkan kepribadian yang terpuji. Penelitian ini bertujuan mengembangkan suplemen bahan ajar akhlak untuk siswa sekolah dasar yang berfokus pada pembentukan akhlak terhadap diri sendiri dan sesama manusia. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE, yang meliputi lima tahap: analisis kebutuhan, desain awal, pengembangan melalui validasi ahli, implementasi dengan saran praktisi, dan evaluasi akhir. Hasil penelitian menunjukkan bahwa suplemen bahan ajar yang dikembangkan memperoleh nilai kelayakan dari ahli bahasa (87%), ahli materi (91%), ahli desain (95%), dan guru (84%), dengan rata-rata keseluruhan 89%. Simpulan dari penelitian ini adalah bahwa suplemen bahan ajar akhlak yang dikembangkan layak digunakan untuk meningkatkan pemahaman siswa terhadap pembelajaran akhlak di sekolah dasar.